2009
DOI: 10.1017/s0047279408002584
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity and Fertility in Italy and Spain

Abstract: Gender equity and its effects on fertility vary across socio-political contexts, particularly when comparing less with more developed economies. But do subtle differences in equity within more similar contexts matter as well? Here we compare Italy and Spain, two countries with low fertility levels and institutional reliance on kinship and family, but with employment equity among women during the 1990s slightly greater in Italy than Spain. The European Community Household Panel is used to explore the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 31 publications
9
87
0
8
Order By: Relevance
“…In couples where only the father is employed, there are fewer tasks shared at least equally than in couples with a dual income. As noted by many authors Cooke, 2009), a key factor for greater equality in the sharing of domestic tasks is an equal relationship in the labor market. However, in this model income differences in the couple do not have effects on the level of equality in the division of tasks in the domestic sphere.…”
Section: Effect Of the Use Of Paternity Leave On The Division Of Domementioning
confidence: 95%
See 2 more Smart Citations
“…In couples where only the father is employed, there are fewer tasks shared at least equally than in couples with a dual income. As noted by many authors Cooke, 2009), a key factor for greater equality in the sharing of domestic tasks is an equal relationship in the labor market. However, in this model income differences in the couple do not have effects on the level of equality in the division of tasks in the domestic sphere.…”
Section: Effect Of the Use Of Paternity Leave On The Division Of Domementioning
confidence: 95%
“…Aparte de los efectos de los permisos de paternidad en el reparto de tareas reproductivas por parte de los varones, en el presente estudio se revisan los infl uidos por otros factores, que tienen un impacto positivo en el reparto más igualitario de las tareas domés-ticas, y que se encuentran recogidos en la revisión bibliográfi ca de Lachance-Grezela y Bouchard (2010), tales como: los ingresos relativos positivos de la mujer (Naldini et al, 2009;Pinto y Coltrane, 2009); un mayor nivel educativo por parte de los hombres (Gershuny y Sullivan, 2003); una menor participación del hombre en el trabajo remunerado (Gauthier et al, 2004;Gauthier y DeGusti, 2012;Hook, 2006;Pinto y Coltrane, 2009) y la participación de ambos miembros de la pareja en el mercado laboral (Cooke, 2009). También se comentan los efectos del permiso de paternidad por la variable de valores igualitarios respecto al cuidado, que pueden incrementar las horas de trabajo doméstico (Bianchi et al, 2000), así como se advierte sobre la disminución de la participación en el cuidado de niños por el hecho de disponer de servicio doméstico (González y JuradoGuerrero, 2009).…”
Section: Haas Y Hwangunclassified
See 1 more Smart Citation
“…Those studies focusing on the micro-level of sharing of household tasks (i.e., actual division of household work) tend to find a positive association of gender equality with both fertility intentions and fertility behaviour (e.g., Cooke 2008;Mills et al 2008;Oláh 2003;Tazi-Preve, Bichlbauer, and Goujon 2004;Torr and Short 2004). The burden of domestic care more frequently lies with the female partner even in the most advanced societies, but is nevertheless mitigated by several couple characteristics.…”
Section: Gender Equality and Fertilitymentioning
confidence: 99%
“…Indeed, familyfriendly services and policies matter for fertility and probably correlate with the extent that household tasks are shared. When comparing Italy and Spain during the 1990s by means of the European Community Household Panel, Cooke (2008) concluded that increased equality in women's employment increased not only the degree of equality within the home but also the likelihood of having a second birth. More specifically, access to private childcare significantly increased the chance of childbearing in Spain, whereas a larger amount of childcare carried out by the father produced the same effect in Italy, particularly among employed women.…”
Section: Gender Equality and Fertilitymentioning
confidence: 99%